β-amyloid accumulation enhances microtubule associated protein tau pathology in an APPNL-G-F/MAPTP301S mouse model of Alzheimer’s disease - Jiang, Lulu; Roberts, Rebecca; Wong, Melissa; Zhang, Lushuang; Webber, Chelsea Joy; Libera, Jenna; Wang, Zihan; Kilci, Alper; Jenkins, Matthew; Ortiz, Alejandro Rondón; Dorrian, Luke; Sun, Jingjing; et al. (Frontiers in Neuroscience, 2024)
The study for the pathophysiology study of Alzheimer's disease (AD) has been hampered by lack animal models that recapitulate the major AD pathologies, including extracellular -amyloid (A) deposition, intracellular aggregation of microtubule associated protein tau (MAPT), inflammation and neurodegeneration. We now report on a double transgenic APPNL-G-F/PS19 MAPTP301S mouse that at 6 months of age exhibits robust A plaque accumulation, intense MAPT pathology, strong inflammation and extensive neurodegeneration. The presence of A pathology potentiated the other major pathologies, including MAPT pathology, inflammation and neurodegeneration. MAPT pathology neither changed levels of amyloid precursor protein nor potentiated A accumulation. Interestingly, study of immunofluorescence in cleared brains indicates that microglial inflammation was generally stronger in the hippocampus, dentate gyrsu and entorhinal cortex, which are regions with predominant MAPT pathology. The APPNL-G-F/MAPTP301S mouse model also showed strong accumulation of N6-methyladenosine (m6A), which was recently shown to be elevated in the AD brain. m6A primarily accumulated in neuronal soma, but also co-localized with a subset of astrocytes and microglia. The accumulation of m6A corresponded with increases in METTL3 and decreases in ALKBH5, which are enzymes that add or remove m6A from mRNA, respectively. Thus, the APPNL-G-F/MAPTP301S mouse recapitulates many features of AD pathology beginning at 6 months of aging.